(untitled) (World Bulletin of Management and Law, 2022)
Nowadays, the provision of human rights is the most important task of the state in Uzbekistan, as well as in many democratic countries. It is known that improving the activities of state authorities, especially local state authorities, and increasing the role of civil society institutions in the implementation of human rights is an important issue. In this article, the issues of further improvement of the activity of party structures, party groups in local councils, creation of modern legal mechanisms and effective guarantees are scientifically analyzed.